Organizational and activity games as a means of developing entrepreneurial competence of future economists (Pedagogy of Higher and Secondary Education, 2014)
Matukova G. I. Organizational and activity games as a means of developing entrepreneurial competence of future economistsThe article is devoted to the description of the methodology of the organizational and activity games that are aimed at personal development of future specialists, their experience in an interdisciplinary way to solve professional problems. The author reveals the content of the organizational and activity game “Regional business project” conducted by the author within the framework of preparing for the high school contest of business plans defense with the aim to develop the entrepreneurial activity of future business economists.
Keywords: competence in entrepreneurship; organizational and activity game; entrepreneurial competence; training of future economists; interdisciplinary solution to professional problems